Moral of Educational Leaders Based on Religious, Philosophy, Psychology and Sociology - Muhtar, Zaenal; Sauri, Sofyan; Fatkhullah, Faiz Karim; Aryani, Iin; Yudianti, Maria Susana (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
The existence of a leader greatly determines the progress and retreat of a country. This research uses descriptive qualitative research methods using literature study as data collection technique. Based on analysis data, the essence of leadership in the view of Islam can be defined as the trust which must be carried out well and held accountable not only in this world but also before Allah. According to Philosophy, a moral leader can do job based on deep way of thinking. According to Psychology, the leadership style of moral person influences the process of his daily life. According to Sociology, moral of educational leadership is greatly influenced by social conditions of society and its institutions. The application of leadership moral in educational institution is barometer of achieving success or not and has implication to the educational process. This research adds important value that must exist in an educational leader who is guided by the foundations of religion, philosophy, psychology and sociology.